Yoga in Lung Cancer Care: A Scoping Review of Randomized Clinical Trials and Outcomes - Giridharan, S (International Research Journal of Ayurveda & Yoga, 2024)
Background: Lung cancer, a leading cause of cancer-related morbidity and mortality worldwide, necessitates innovative therapeutic approaches to enhance patient outcomes. Yoga, an ancient practice with multifaceted benefits, has shown promise in cancer care but remains underexplored in lung cancer. Methods: This scoping review focused on randomized trials from 2014 to 2023, examining yoga interventions in lung cancer care. We conducted a comprehensive literature search across PubMed, Cochrane, Embase, and CINAHL. The selection involved screening for relevance and detailed data extraction on study characteristics. Results: The review identified three studies that met the inclusion criteria, highlighting notable benefits such as short term pulmonary enhancements, significant physical and social function improvements for patients and caregivers, and perioperative benefits such as reduced dyspnea and anxiety. Conclusion: Preliminary evidence suggests yoga could be a valuable adjunct therapy in lung cancer treatment. However, the heterogeneity in study designs and small sample sizes highlight the need for further, more rigorous research to establish standardized yoga protocols for lung cancer care.